Delegated investment decisions and rankings - Kirchler, Michael; Lindner, Florian; Weitzel, Utz (Journal of Banking & Finance, 2020)
Two aspects of social context are central to the finance industry. First, financial professionals usually make investment decisions on behalf of third parties. Second, social competition, in the form of performance rankings, is pervasive. Therefore, we investigate professionals’ risk taking behavior under social competition when investing for others. We run online and lab-in-the-field experiments with 805 financial professionals and show that professionals increase their risk taking for others when they lag behind. Additional survey evidence from 1349 respondents reveals that professionals’ preferences for high rankings are significantly stronger than those of the general population.